1962
DOI: 10.1001/jama.1962.03050050012003
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Potential of Adenomas of Colon and Rectum

Abstract: A few inflammatory polyps or retention polyps were found that had been originally diagnosed as adenomatous polyp, and these were excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
2

Year Published

1963
1963
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(14 citation statements)
references
References 1 publication
2
9
1
2
Order By: Relevance
“…As the size of adenomas increases, so does the grade of dysplasia, in agreement with previous studies [4,22,24]. Size is the most simple and practical indicator and is closely related to grade of dysplasia.…”
Section: Size and Grade Of Dysplasiasupporting
confidence: 91%
See 1 more Smart Citation
“…As the size of adenomas increases, so does the grade of dysplasia, in agreement with previous studies [4,22,24]. Size is the most simple and practical indicator and is closely related to grade of dysplasia.…”
Section: Size and Grade Of Dysplasiasupporting
confidence: 91%
“…It has been stated that villous adenomas are located almost exclusively in the rectum [22,23]. In contrast, our study has shown that both tubulovillous and villous adenomas are more widely distributed with only a slightly higher incidence in the rectum and in the sigmoid colon.…”
Section: Histologic Typescontrasting
confidence: 85%
“…In addition, because this study included prevalent, rather than incident, polyps, it is not possible to discriminate between factors affecting the risk and the duration of polyps. However, factors that affect duration may also be important, because larger polyps, which are probably of a longer duration, may be more likely to undergo malignant transformation (Enterline et al, 1962;Hoff et al, 1987). Despite the potential limitations of the study, however, the response rates were high for both the case and control groups, and with nearly 500 case-control pairs, this is among the largest studies of risk factors for colorectal polyps.…”
Section: Discussionmentioning
confidence: 85%
“…Because adenomatous polyps are likely precursors of colorectal carcinoma (Enterline et al 1962;Stryker et al, 1987;Jass, 1989;Pollock and Quirke, 1991), research has focused on risk factors for colorectal adenomas in recent years. Many studies have reported protective associations of physical activity with risk of colorectal adenomas (Kato et al, 1990; Kono et al, 1991;Benito et al, 1993;Giovannucci et al, 1996), and others have demonstrated more modest protective associations (Little et al, 1993;Giovannucci et al, 1995;Sandler et al, 1995).…”
mentioning
confidence: 99%
“…The rate of malignant transformation in the 46 villous adenomas of the duodenum reported to date was about 36%, somewhat less than the rate in the colon and rectum (55%) reported by Ente~line et al [8], but still definitely establishing the premalignant nature of villous gastrointestinal tumors regardless of location. …”
Section: Discussionmentioning
confidence: 58%